2018
DOI: 10.3390/md16060184
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of MAG-DHA for Correcting AA/DHA Imbalance of Cystic Fibrosis Patients

Abstract: Omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementations are thought to improve essential fatty acid deficiency (EFAD) as well as reduce inflammation in Cystic Fibrosis (CF), but their effectiveness in clinical studies remains unknown. The aim of the study was to determine how the medical food containing docosahexaenoic acid monoglyceride (MAG-DHA) influenced erythrocyte fatty acid profiles and the expression levels of inflammatory circulating mediators. We conducted a randomized, double blind, pilot tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
(43 reference statements)
0
9
0
2
Order By: Relevance
“…Significant EPA increments were observed after feeding subjects 2 g capsule of fish oil (3.2 g EPA and 2.2 DHA) daily for 6 weeks. In a 60-day trial, feeding MAG-DHA (8 × 625 mg MAG-DHA) daily showed an increased DHA levels and a decreased AA ratio (AA/DHA) in erythrocytes [39,55]. Feeding DHA from algal oils has also resulted in significant increments of DHA in plasma, erythrocytes, and rectal DHA levels [56,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant EPA increments were observed after feeding subjects 2 g capsule of fish oil (3.2 g EPA and 2.2 DHA) daily for 6 weeks. In a 60-day trial, feeding MAG-DHA (8 × 625 mg MAG-DHA) daily showed an increased DHA levels and a decreased AA ratio (AA/DHA) in erythrocytes [39,55]. Feeding DHA from algal oils has also resulted in significant increments of DHA in plasma, erythrocytes, and rectal DHA levels [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, OM3 was shown to be an effective substrate to MGAT enzyme and could be used as a pre-digested fat [37,38] with potentially improved bioavailability compared to ethyl ester or TAG. This lipase-independent MAG carrier may offer a clinical advantage to patients struggling with fat malabsorption/maldigestion problems, for instance, patients with cystic fibrosis [21,[37][38][39].…”
Section: Eementioning
confidence: 99%
“…Foods higher in omega-3 fatty acids may help improve the imbalance of omega-3 to omega-6 fatty acids and potentially improve inflammatory markers, but there is insufficient evidence to recommend supplements at this time. [30,31] A variety of high-fat foods are recommended, including polyunsaturated and monounsaturated fats. These can include butter, cheese, cream, olive oil, dressings, sauces, fatty fish, nuts and nut butters, seeds, and fatty vegetables (avocados).…”
Section: Fatsmentioning
confidence: 99%
“…Monoglycerides from omega-3 polyunsaturated fatty acid PUFA were also beneficial effects to some human disorder condition such as cancer and inflammation disease 26 . Monoglycerides from EPA and DHA are likewise very useful for human health base on their nutritive value 6 , role in there regulation of inflammation, cholesterol metabolism, and brain functions 27 , their influence to erythrocyte fatty acid profiles and the expression levels of inflammatory circulating mediators 28 . Long Chain Poly Unsaturated Fatty Acid LC-PUFA monoglycerides oil also increased LC-PUFA levels in erythrocytes, plasma, and chylomicrons 29 .…”
mentioning
confidence: 99%